Oncogenic challenge of bromocriptine and L-arginine versus conventional antidiabetics on diethyl nitrosamine-induced liver tumorigenesis in diabetic rats: focus on AMPK activation - Hewedy, Wafaa A.; Anwar, Eman I.; Sharara, Gehan M.; Hadi, Mona A.; Darwish, Suzan A.; Ismail, Cherine A. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Diabetes mellitus (DM) is associated with a spectrum of cancers where the metabolic antecedents, consequences, and therapy might affect cancer risk. The association between hepatocellular carcinoma (HCC) and DM had been confirmed. Approaches to HCC prevention focus on the molecular regulators of the disease process defined as the inflammation-fibrosis-cancer axis. The AMP-activated protein kinase (AMPK) is an interesting metabolic tumor suppressor and a promising target for cancer prevention and therapy. This study aimed to investigate the effects of bromocriptine mesylate and L-arginine on hepatic carcinogenesis on a rat model of hepatic neoplasia induced by diethyl nitrosamine (DENA) and promoted by type-2 DM in contrast to the conventional antidiabetics. Methods: One hundred male Wistar rats were randomly assigned into two sets; control set (normal, HCC, DM, and combined HCC/DM) and treated set where rats received one of the following drugs for another 5 weeks: insulin glargine, glimepiride, metformin, pioglitazone, bromocriptine mesylate, or L-arginine. Bodyweight changes, blood glucose level, liver functions tests, serum C-peptide and alpha-fetoprotein (AFP), and hepatic activated AMPK were assessed beside the hepatic histopathological changes. Results: Equivalent to metformin, bromocriptine and L-arginine treatment significantly reduced AFP, despite their minor glycemic control. L-arginine induced AMPK activation, yet less than metformin. Histopathologic examination revealed a reduction in hepatic intra-lobular chronic inflammatory cell infiltration, steatosis and necrosis by metformin, bromocriptine, and L-arginine. Hepatic necro-inflammatory changes were most prominent in insulin-treated rats. Conclusions: L-arginine and bromocriptine mesylate prevent early neoplastic changes almost equivalent to metformin at least partially via hepatic AMPK activation.